RESPONSE OF DURUM WHEAT ( Triticum aestivum L.) TO FOLIAR APPLICATION OF MICRONUTRIENTS IN SALTED AND CALCAREOUS SOIL - M iloudi, B; M asmoudi, A; M asmoudi, M.C h (university of el oued/جامعة الوادي, 2021)
The alkaline nature of arid regions soil usually posses a reduction in solubili ty and assimi lability of micronutrient in soil. A study has been carried out to focus on the effect of foliar spraying of micronutrients (Fe, Zn, Cu, Mn, Mo ) on wheat cultivation in a saline and calcareous soil. Th e studied growth parameters are stem len gth, yield, w eight of 1000 seeds and weight of dry matter. According to ANOVA at 5% the fo llowing results were obtained : the Zn+Cu 87.67cm , Cu+Mn 83.63cm, Fe+Zn+Cu+Mo 83.53cm treatments exerted the best lengths in succession. For dry matter, the best treat ments reporte d are Zn+Cu+Mo 12396.00Kg/ha, Fe+Mn+Mo11614.67Kg/ha and Fe+Zn+Cu+Mn 11415.67Kg/ha. The results of the weight of 1000 seeds are arranged as follows: Cu+Mo 44.62g was the greatest followed by, Zn+Mo 42.97g, and then by Zn+Cu+Mn+Mo 42.85g. The to pranked trea tments in the yield parameter are Fe+Mo 3480.00 Kg/ha, followed by Fe+Zn+Cu+Mn 3451.00 Kg/ha, and then Mn+Mo 3442.20 Kg/ha.
Article
Keywords: Keywords: foliar spraying; micronutrients ; Salted calcareous soils ; Wheat ; pH ; alkaline reaction.